Thermomechanical-induced polyelectrolyte complexation between chitosan and carboxymethyl cellulose enabling unexpected hydrolytic stability. (22nd March 2020) - Chen, Pei; Xie, Fengwei; Tang, Fengzai; McNally, Tony
Abstract: Natural biopolymers such as chitosan and cellulose have demonstrated huge potential in important and rapidly growing environmental and biomedical applications. However, it is always challenging to create advanced functional biopolymer materials with enhanced hydrolytic stability cost-effectively. Here, we report an advance in preparing biopolymer polyelectrolyte complexed materials based on chitosan and carboxymethyl cellulose (CMC) using a "dry", thermo-mechanical kneading method. Despite the high hydrophilicity of chitosan and CMC, the resulting films showed excellent dimensional stability and structural integrity (27% dimensional expansion and 94% weight increase after hydration for one day). In comparison, chitosan-only films were swollen dramatically under the same conditions, with a 138% dimensional expansion and a 913% rise in weight, which were also fragile. We propose that our processing method led to polyelectrolyte complexation between chitosan and CMC generating physical crosslinking points in the materials, which stabilised the films in water. Interestingly, the greater hydrolytic stability of chitosan/CMC films is in contrast with their higher surface hydrophilicity, a contribution from CMC. Our simple approach to engineering high-performance biopolymer materials without resorting to complex chemistries can be envisioned to bring about a new direction in the design of advanced functional materials where sustainability and cost-effectiveness are priorities. Graphical abstract: Image 1 Highlights: Composites of chitosan/carboxymethyl cellulose (CMC)/nanoclay prepared. Thermomechanical processing led to polyelectrolyte complexation between chitosan and CMC. Chitosan/CMC films were more hydrolytically stable than chitosan-alone films. Chitosan/CMC films had higher surface hydrophilicity than chitosan-alone films. Chitosan/CMC complexed materials have potential for biomedical applications.